Laboratory hematology practice - Kottke-Marchant, Kandice; Davis, Bruce H., M.D.; International Society for Laboratory Hematology (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley-Blackwell/International Society for Laboratory Hematology, 2012)
Expertly edited and endorsed by the International Society for Laboratory Hematology, this is the newest international textbook on all aspects of laboratory hematology. Covering both traditional and cutting-edge hematology laboratory technology this book emphasizes international recommendations for testing practices. Illustrative case studies on how technology can be used in patient diagnosis are included. Laboratory Hematology Practice is an invaluable resource for all those working in the field.
33. :ClottingFactorsandInhibitors:AssaysandInterpretation -- 34. :DiagnosisofvonWillebrandDisease -- 35. :DiagnosisofFibrinolyticDisorders -- 36. :LaboratoryEvaluationofAcquiredCoagulationDisorders -- 37. :PlateletAssaysandPlateletDysfunction -- 38. :Thrombophilia:AssaysandInterpretation -- 39. :LupusAnticoagulants, AntiphospholipidAntibodies, andAntiphospholipidSyndrome -- 40. :Heparin-InducedThrombocytopenia -- 41. :Anticoagulant, Antiplatelet, andThrombolyticDrugs -- 42. :GuidelinesforEvaluationofCoagulationAnalyzersandCoagulationTesting -- 43. :EssentialsofImmunohematology.
Includes bibliographical references and index.
Keywords: Hematology; Blood -- Analysis; Hematologia; Electronic books; Llibres electrònics.